Gaps between Theory and Practice: Novice Teachers’ Perspectives - Syeda Tehzeeb Alvi; Muhammad Shahid Zulfiqar Ali; Fahan Ahmad (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This study aimed to explore the novice teachers’ perception of gaps between theory and practice. Novice teachers’ perceptions were further explored based on teachers’ gender. The survey method was used to collect the data. A questionnaire was developed by the researcher consisted of 39 items with 5 points Likert rating scale to collect data from randomly selected 600 teachers including male and female. The data were analyzed by using the mean, standard deviation, and percentage of each five points of the Likert rating scale. The results revealed that most novice teachers were applying their learned theory in their practice regarding lesson planning & delivery, classroom management, and students’ active involvement. They were not only willing to but also were applying learned theories in their practice. It also came into the knowledge that there were fewer gaps between novice teachers’ theory and practice. It is recommended by the researchers suggested that these pre-service training centers should develop a strong and viable link to make the theory more practical, operational and up-to-date